La Neurosis: Un Estudio Desde La Subjetividad - Arroyo, José Manuel García (European Scientific Journal, ESJ, 2016)
The disappearance of the neurosis of current psychiatric nosography has caused at least two effects: a) the dispersion of psychiatric clinical categories, as can be seen in modern classifications b) the disappearance of the subject in our discipline. This article aims not only to recover the neurosis as a diagnostic category, but understand it as a "structure" and, on this basis, obtain the keys to the "neurotic subjectivity." To achieve this, we use a method that simultaneously allows the study of the "inner" and make it a scientific matter. Although it is considered, in the neurotic person the existence of a right "reality testing", it can not avoid considering the outside world in part, according to personal expectations. We have called this "objective collapse" and it realizes that there is no "objectivity" as believed in these patients. Hence, is there a neurotic way of knowing in which easily a confusion between "subjectivity", "subjective" and "objective" occurs.